Stratification of venous thromboembolism risk in burn patients by Caprini score. Issue 1 (February 2019) - Li, Quan; Ba, Te; Wang, Ling-Feng; Chen, Qiang; Li, Fang; Xue, Yuan
Highlights: Caprini score was used to evaluate venous thromboembolism risk in burn patients. Thirteen patients (0.67%) had venous thromboembolism among 1939 inpatients. Venous thromboembolism (8.82%) occurred most commonly in the group with Caprini score >8. Abstract: Background: The purpose of the research was to determine the efficacy of the Caprini risk assessment model for the guidance of prophylactic treatments for a 3-year period in the burn center of the Inner Mongolia region. Methods: From July 2014 to August 2017, the Caprini score for every admitted patient was calculated to evaluate venous thromboembolism (VTE) risk. Subjects with a Caprini score between 0 and 2 were not administered a chemical VTE prophylaxis, and subjects with a score of 3 and above were administered low-molecular-weight heparin (LMWH). Demographic information, abbreviated burn severity index (ABSI) score, body mass index (BMI), Caprini score, full-thickness total body surface area (TBSA), overall TBSA, day of ambulation, hospital stay, inhalation injury, electrical burn, central venous catheters, and operations were noted for analysis. Results: Of 1939 inpatients during the study period, 13 patients (0.67%) had VTE complications. The interval from injury to VTE diagnosis was 13.9 ± 8.7 days. Among patients (n = 1131) with a Caprini score between 0 and 2, two patients (0.18%) had VTE. A total of 792 patients received LMWH thromboprophylaxis; 11 patients had VTE complications, and among them, one patient (0.13%) developed heparin-induced thrombocytopenia and two patients (0.25%) developed major bleeding. VTE (8.82%) occurred most commonly in the Caprini score >8 group. Age, Caprini score, ABSI score, overall and full-thickness TBSA, central venous catheters, day of ambulation, and hospital stay in patients with VTE (n = 11) were significantly higher than those (n = 781) without VTE (p < 0.05). Conclusions: Caprini score allows for informed decision-making regarding prophylaxis strategies. Early ambulation and mechanical prophylaxis are recommended for patients predisposed to VTE.